Coaches' perspectives of the continuing coach education program in the development of quality coach education in Singapore - Tan, L. Q. W.; O`Connor, D. (International Sport Coaching Journal, 2023)
Continuing professional development is considered essential to the improvement of sport coaching standards through the development of coaches` knowledge. To support continuing professional development participation and learning for Singapore coaches, the Continuing Coach Education (CCE) program was introduced by Sport Singapore. The present study examined the influence of the Continuing Coach Education program on Level 1 Singapore-based coaches registered under the National Registry of Coaches. Utilizing an explanatory sequential quantitative-qualitative mixed methods approach to enhance understanding of participants` perceptions, National Registry of Coaches Level 1 coaches completed an online questionnaire (n = 124) and participated in a semistructured interview (n = 7). Results revealed: (a) that intrapersonal knowledge was valued over professional and interpersonal knowledge; (b) that holistic development with an emphasis on character development of athletes was valued; (c) coaches` key learning needs (i.e., sport psychology, use of technology in coaching, and career planning and development); (d) a preference to experience various learning sources (i.e., collaborative, experientially driven, recognized mediated, and internal unmediated), specific learning sources (i.e., self-directed and guided experiential), and improved coach developer facilitation; and (e) main learning motivations (i.e., meeting requirements and content relevance) and barriers (i.e., time and cost). Possible strategies to promote continuing professional development participation and learning for coaches practicing in similar contexts are discussed.